2018
DOI: 10.3390/c4010004
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy of Carbon: A Brief History

Abstract: Transmission electron microscopy (TEM) has been used in the study of solid carbon since the 1940s. A number of important forms of carbon have been discovered through the use of TEM, and our understanding of the microstructure of carbon has largely been gained through the application of TEM and associated techniques. This article is an attempt to present an historical review of the application of TEM to carbon, from the earliest work to the present day. The review encompasses both graphitic carbon and diamond, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 87 publications
2
24
0
1
Order By: Relevance
“…The separation distance between walls of adjacent nanotubes was estimated to be 0.34 nm. However, many years before the Iijima discovery, in 1976, Oberlin et al [99] presented similar TEM images, which are shown in Figure 28b. The resolution of electron microscopes available at that time did not allow to "see" the structure of carbon walls in such objects and the Iijima HRTEM observations led to correct description of the CNT structure.…”
Section: Carbon Nanotubes and Graphenementioning
confidence: 81%
See 1 more Smart Citation
“…The separation distance between walls of adjacent nanotubes was estimated to be 0.34 nm. However, many years before the Iijima discovery, in 1976, Oberlin et al [99] presented similar TEM images, which are shown in Figure 28b. The resolution of electron microscopes available at that time did not allow to "see" the structure of carbon walls in such objects and the Iijima HRTEM observations led to correct description of the CNT structure.…”
Section: Carbon Nanotubes and Graphenementioning
confidence: 81%
“…Review articles on application of TEM for structural studies of carbon nanomaterials have been already published [94][95][96][97][98][99]. Therefore, in the last two sections we will focus only on some selected issues which may be confronted with achievements of powder XRD and ND in characterization of carbon nanotubes, graphene, nanodiamonds, and nanoonions.…”
Section: Carbon Nanotubes and Graphenementioning
confidence: 99%
“…Most of the spectra presented a 2D/G ratio lower than one, as shown in Figure 3. Nevertheless, the 2D peak related to this distribution fitted with multiple Lorentians (2-4), suggesting the presence of a few graphite layers (mostly bi and three-layered) [25,26]. On the other side, it is worth noticing that films with a concentration of 33% of graphene showed as well normally distributed features owing to the graphene.…”
Section: Ramanmentioning
confidence: 91%
“…Thin section of the sample was prepared by a process known as ultramicrotomy, sections of 50-70 nm thickness were collected on metal mesh 'grids'; and TEM studies were performed (25,26) .…”
Section: Transmission Electron Microscopymentioning
confidence: 99%